Titanium dioxide‐coated biochar composites as adsorptive and photocatalytic degradation materials for the removal of aqueous organic pollutants. Issue 3 (20th October 2017) - Cai, Xiaoxi; Li, Jiang; Liu, Yunguo; Yan, Zhili; Tan, Xiaofei; Liu, Shaobo; Zeng, Guangming; Gu, Yanling; Hu, Xinjiang; Jiang, Luhua
Abstract: BACKGROUND: This article reports the synthesis and characterisation of titanium dioxide‐coated biochar composites (TBCs) by pyrolysing titanium dioxide‐treated biomass prepared by a modified sol–gel method. Their adsorptive and photocatalytic activities were evaluated based on the removal of safranine T (ST) from an aqueous solution with/without UV‐light irradiation. RESULTS: Characterisation studies suggested that TiO2 was successfully loaded on the biochar substrate. The biochar and TiO2 contents of the composite significantly affected its performance. The ST removal capabilities of the TBCs with 1, 1.5, 2, and 2.5 g of the biomass are 1.7, 2.3, 7.2, and 2.3 times better than that of the raw biochar, respectively. Thus, the optimum amount of biomass in TBC‐x was determined to be 2 g, with the corresponding sample exhibiting excellent stability, effectiveness over a wide pH range, and a maximum ST removal capacity of 226.7 mg g ‐1 . CONCLUSION: The loading of TiO2 significantly enhanced the adsorption performance of biochar and the high specific surface area of the biochar synergistically promoted the photocatalytic activity of TiO2 . Both adsorption and photocatalytic degradation were confirmed to contribute to the decolourisation of the aqueous solution because of the removal of ST, with the effect of adsorption being slightly higher than that of photocatalysis. The synthesised composite is a promising alternative material for removing chemical contaminants. © 2017 Society of Chemical Industry